Pengaruh Public Relations dan Personal Selling Terhadap Brand Awareness Produk Skincare Glad2Glow - Intan Nabila; Zulfadil Zulfadil (eCo-Buss, 2026)
The purpose of this research is to analyze how Glad2Glow skincare product brand recognition changed after using PR and direct sales strategies. Brand awareness represents a crucial element in shaping consumer perceptions, influencing purchase considerations, and fostering long-term customer loyalty, particularly among younger consumer segments. One hundred members of Generation Z in Pekanbaru were chosen using a non-probability selection method based on a purposive sampling strategy for this quantitative study. The researchers used multiple linear regression to assess the independent factors' partial and simultaneous impacts on brand awareness, with data acquired via structured questionnaires. The results show that PR does increase brand recognition to a certain extent, and that this effect is positive and statistically significant. This shows that communication efforts that focus on establishing rapport, trust, and a positive image of the brand are crucial for raising brand awareness and memorability. Contrarily, there is no evidence that personal selling increases brand recognition, implying that direct interpersonal communication strategies may not be the primary factor influencing brand recognition among Generation Z consumers. Simultaneously, public relations and personal selling contribute 43% to brand awareness, aside from other factors that are not covered in this research, which accounts for 57%. In short, the findings show that PR is more important than ever before in raising brand recognition among millennials and Gen Zers.